A multicentre retrospective review of SABR reirradiation in rectal cancer recurrence. (September 2021) - Johnstone, Philippa; Okonta, Leroy; Aitken, Katharine; Holmes, Jane; Harrison, Mark; Harji, Deena; O'Cathail, Sean M.; Taylor, Claire; Tsang, Yat; Wing, Mark; Muirhead, Rebecca
Highlights: The optimal non-surgical management for LRRC is unknown. Median OS after SABR reirradiation is encouraging. Optimization of SABR for LRRC could further improve QoL and outcomes. Further data is required before SABR is established as an alternative to surgery. Abstract: Background and purpose: Locally recurrent rectal cancer (LRRC) is associated with considerable morbidity, poor quality of life and an overall survival of 9 months. The non-operative treatment of LRRC is an understudied area, there is no consensus on management in this setting. We aim to perform a retrospective, multicentre analysis of patients treated with SABR reirradiation. Materials and methods: All patients were identified who received SABR re-irradiation for LRRC, at 3 UK centres, between August 2015 and September 2020. Eligible patients had pelvic recurrence and were either not suitable/opted not for surgery, or margin positive after exenturative surgery. Patients were treated with 30 Gy in 5 fractions and followed up with clinical review and CT scan at 3, 6, 12, 18 and 24 months. Results: 69 patients with 81 lesions were identified and median follow up was 28 months. Median progression free survival (PFS) and overall survival (OS) were 12.1 months (10.4, 17.7) and 38.7 months (28.9, -) respectively. 2-year OS was 0.77 (0.66, 0.89). 58.3% of deaths were as a result of consequences of local relapse. 42.6% of patients had local relapse at death or last follow up. Conclusion: Our outcomes are encouraging for a population who had R1 resections, refused or were refused surgery; as they are similar to those in surgical series. Prospective data including details of survival, local relapse and QOL; with an optimised SABR technique, is required to establish SABR as an alternative to surgery.